Synthesis of Metronidazole Derivatives Containing Pyridine Ring and Anticancer Activity - Yong, Jianping; Lu, Canzhong; Wu, Xiaoyuan (Letters in Organic Chemistry, 2016)
Background: Cancer is a major health problem worldwide, the relative mortality rate caused by cancer is still very high in developed countries. Although the remarkable success has been achieved: more than 15 small molecule anticancer agents have been approved by the U.S. Food and Drug Administration (FDA) in clinics and dozens are currently in clinical trials, cancer chemotherapy is still highly inadequate, and it is essential to find novel structures, low side effect and more potent anticancer agents. Metronidazole derivatives exhibited widely biological activities, such as: antibacterial, antiinflammatory, anti-parasitic, α-glucosidase inhibition, antitubercular, antimycobacterial, antimicrobial, and anticancer activity. Based on our previous research, we synthesized a series of metronidazole derivatives in current work for the development of anticancer agents. Methods: The target compounds were prepared by the reaction of metronidazole with the R-substituted-pyridine-carboxyl acid in dry THF, catalyzed by DCC, HOBt/DMAP. And then, the in vitro anticancer efficacy against A549, HCT116 and MCF-7 cell lines was evaluated, and the anticancer efficacy was comparable with the reference drug gefitinib. Results: The structures of the target compounds were fully characterized using NMR, MS and XRD. The biological evaluation showed that all compounds exhibited good anticancer activity against A549, HCT116 and MCF-7 cell lines. Conclusion: From these biological results, we can get some rules: (1) The derivatives of carboxyl group at the 3-position of pyridine ring are much stronger than others (carboxyl group at the 4-position and 2-position of pyridine ring); (2) Introduction of the large volume group at the pyridine ring will improve the anticancer efficacy too much. This guidance helps us to design and synthesize more metronidazole derivatives for development of anticancer agents.
Keywords: metronidazole derivatives